A Novel Approach for Bioleaching of Sulfur, Iron, and Silica Impurities from Coal by Growing and Resting Cells of Rhodococcus spp. Issue 2 (7th February 2019) - Etemadifar, Zahra; Etemadzadeh, Shekoofeh Sadat; Emtiazi, Giti
Abstract: Coal is one of the most important sources of fossil energy on earth. However, direct combustion of coal with a high sulfur content can cause various environmental problems. Other constituents of coal that can cause environmental problems include iron oxide (hematite), iron hydroxide, and silica. In this study, growing and resting cells of Rhodococcus erythropolis strains PD1, R1, and FMF, and R. qingshengii were used in heterotrophic removal of sulfur and bioleaching of iron and silica from coal. All of the mentioned strains have an ability of dibenzothiophene (DBT) desulfurization via 4-S pathway. 2-hydroxybiphenyl, sulfate, and ferric ions (Fe 3+ ) were assayed by Gibb's test, barium chloride (BaCl2 ), and thiocyanate ions (SCN − ), respectively. FTIR and XRF analyzer were used for detection of the coal bioleaching process by the selected strain of R. erythropolis (PD1). Results indicated that all strains have the ability to grow on coal as the sulfur source. Among them, strain PD1 produced the highest optical density and continued to grow even after 150-h incubation. In both growing- and resting-cells experiments, strain PD1 desulfurized coal most readily compared to other strains. Results of XRF showed that growing cells of strain PD1 had high desulfurizing ability of coal (46%) compared to resting cells in the absence of any carbon sources (24%). Growing cells of strain PD1 also leached 46% of the iron and 14% of the silicate after 7 days of incubation. Resting cells of PD1 leached 32% of the iron as determined by XRF analysis. Also, growing cells of PD1 removed most SiO2 from coal as detected and confirmed by FTIR and XRF. To the best of our knowledge, this is the first report on bioleaching of iron and silica from coal by R. erythropolis strain PD1, making it a suitable candidate for coal bioremediation.